STUDI EVALUASI PENNGELOLAAN ARSIP DI DINAS PERPUSTAKAAN DAN SIP KOTA BANDUNG - Sri Ayu Lestari, - (2019)
Penelitian ini bertujuan mengevaluasi proses pengelolaan arsip di Dispusip Kota Bandung dan sesuai atau tidak dengan standar yang telah ditetapkan yaitu UU No. 43 tahun 2009 tentang Kearsipan dan Peraturan Gubernur No.40 tahun 2008 tentang Tata Kearsipan. Penelitian dilakukan di Dinas Perpustakaan dan Arsip Kota Bandung terletak di Jl. Seram No. 2 Bandung. Penelitian ini menjawab permasalahan penelitian, ialah "Bagaimana proses pengelolaan arsip yang dilakukan di Dinas Perpustakaan dan Arsip Kota Bandung?." Secara khusus rumusan masalah ini terdiri dari: (1) Bagaimana kesesuaian program pengelolaan arsip Dispusip Kota Bandung dilihat dari aspek Context?; (2) Bagaimana Kondisi Faktor penunjang program pengelolaan arsip Dispusip Kota Bandung dilihat dari aspek Input?; (3) Bagaimana pelaksanaan program pengelolaan arsip Dispusip Kota Bandung dilihat dari aspek Process?; (4) Bagaimana keberhasilan program pengelolaan arsip Dispusip Kota Bandung dilihat dari aspek Product?. Metode penelitian yang digunakan ialah statistic deskriptif, dengan menggunakan model evaluasi CIPP. Teknik analisis data menggunakan Kai Kuadrat. Populasi dan sampel penelitian ini adalah seluruh staf bagian pengelolaan arsip Dispusip Kota Bandung. Secara umum, hasil penelitian menunjukann hasil proses pengelolaan arsip yang dilakukan di Dispusip Kota Bandung berjalan baik dan sesuai dengan standar. Simpulan khusus, hasil penelitian menunjukan bahwa proses pengelolaan arsip dilihat dari aspek context, input, process, product dinilai sesuai dengan standar yang ada. Kata Kunci: CIPP, Arsip, Arsiparis, dan Evaluasi ABSTRACT Sri Ayu Lestari(1506595). Study Evaluative Archival Management in Institution of Library and Archival Bandung City. Thesis Library and Information Science Studies Programs. Department of Curriculum and Educational Technology, Faculty of Education. Indonesian University of Education. 2019. This research is an evaluative study which was aimed to evaluate whether the process of archive management implemented in Bandung City Institution of Library and Archival has been suitable or not to the assigned standard in the Constitution No. 43 Year 2009 about the Archival and Governor Rule No 40 Year 2008 about Archival Management of West Java Provincial Government. This research was conducted in Bandung City Institution of Library and Archival which is located in Jalan Seram No. 2 Bandung. This research answered the research question, there is "How is the process of archive management implemented in Bandung City Institution of Library and Archival?. Specifically, the formulations of research questions in this research included: (1) how is the suitability of archive management program in Bandung City Institution of Library and Archival analyzed from the aspect of Context?; (2) How is the condition of supporting factor of archive management program in Bandung City Institution of Library and Archival analyzed from the aspect of input?; (3) How is the implementation of archive management program in Bandung City Institution of Library and Archival analyzed form the aspect of process?; (4) how is the success of archive management program in Bandung City Institution of Library and Archival analyzed from the aspect of product?. This research used quantitative approach, where the research method applied was descriptive statistics with CIPP evaluation model. The technique of data analysis which had been used in this research was Chi Square. Population and sample in this research included archive administrators or achivist in Bandung City Institution of Library and Archival. Generally, the result of the research shows that the process of archive management implemented in Bandung City Institution of Library and Archival has been running well and suitable to the aassigned standard. Specifically, the result show that process of archive management analyzed from the aspecs of context, input, process, and prodruct is well run and suitable to the assigned standard. Keywords: CIPP, Archival, Archivist and Evaluation.